Strategi Pengembangan Sumber Daya Manusia Pada Dosen Universitas Sembilanbelas November Kolaka - Nurhalizah Nurhalizah; Niar Astaginy; Andry Stepahnie Titing (STIKes Ibnu Sina Ajibarang, 2023)
The study aims to determine how the Human Resource Development Strategy at USN Kolaka lecturers works. The study used qualitative methods. Data collection techniques include observation, interviews, and documentation. The informants in this study consisted of key informants (the staffing coordinator) the main informant (5 USN Kolaka lecturers), and supporting informants (2 students). while using data analysis techniques using interactive models, which included data collection, data reduction, data presentation, and conclusion. Based on the results of research, it is known that the lecturers have their own strategies to improve their competence. It is because the strategy applied by the university has not been working effectively. It is because there are several factors that become challenges and obstacles in developing human resources, such as infrastructure, budget, planning, and workload. With inadequate infrastructure and an unrealized budget, lecturers implement their own strategies to improve their competence by attending training or workshops, education, and mentoring.